2016
DOI: 10.1159/000443948
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Stabilization after Delivery in Term Infants after the Update of the Japan Resuscitation Council Guidelines in 2010

Abstract: Background: The Japan Resuscitation Council (JRC) updated the guidelines for neonatal cardiopulmonary resuscitation in 2010, which recommended appropriate oxygen supplementation under the assessment of oximetry, with continuous positive airway pressure (CPAP) as a consideration in the delivery room. Whether this update has resulted in an improvement of respiratory stabilization in term neonates has not been well investigated to date. Objectives: The aim of this study is to evaluate the impact of the update of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The systematic review identified two RCTs 22 , 23 and two observational, before-after studies, one of which was divided into two publications. 24 , 25 , 26 Additional data were obtained from one author and included in this meta-analysis. 24 , 25 Characteristics of included studies are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic review identified two RCTs 22 , 23 and two observational, before-after studies, one of which was divided into two publications. 24 , 25 , 26 Additional data were obtained from one author and included in this meta-analysis. 24 , 25 Characteristics of included studies are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“… 24 , 25 , 26 Additional data were obtained from one author and included in this meta-analysis. 24 , 25 Characteristics of included studies are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We found that the JRC Guidelines 2010 resulted in an increase in the frequency of face mask CPAP use in the delivery room at term birth and a higher prevalence of pulmonary air leak in early‐term neonates . Furthermore, we found that the updated JRC Guidelines 2010 led to an increase of respiratory support in the nursery or NICU within 24 hr after birth . Based on these results, we suggested that face mask CPAP resulted in higher pressure in the alveoli caused by sudden crying or movement of the infant, which led to pulmonary air leak .…”
Section: Introductionmentioning
confidence: 74%
“…We also postulated that CPAP in newborns with transient tachypnea may induce over‐distension of part of the lung through check‐valve mechanism of residual fluid in the peripheral airway, leading to pulmonary air leak . Furthermore, we hypothesized that face mask CPAP leads to increased dead space which might increase work of breathing, which in turn leads to tachypnea or larger tidal volume . The present study was focused and conducted to test this hypothesis.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation